Answer:
3
Step-by-step explanation:
The average rate of change is
f(x2) - f(x1)
-----------------
x2-x1
We want to find the change from 1 to 3
f(3) = 8
f(1) = 2
f(3) - f(1) 8-2 6
----------------- = ------------ = ---- = 3
3-1 2 2
The answer is 3 because since b=-5 you get -5 and add it to 14 giving you 9 and then you divide 9/3 which gives you 3. Hope this helps :)
Answer:
44 Paper wrap; Add all numbers together
Step-by-step explanation:
Hope this helps
Step-by-step explanation:
to work out gradient
change in y ÷ change in x
first lines gradient
(7 - - 8) ÷ (7 - 7) = 0
second lines gradient
(7 - 7) ÷ (9 - - 6) = 0